Developing grammatical competence in French as a second language – between linguistic consciousness and intuition - Piegzik, Wioletta (Glottodidactica, 2022)
The paper proposes a reflection on the construction of grammatical competence in French as L2. We argue that grammatical competence embraces implicit and explicit knowledge, and results from the complementarity of conscious functions, closely linked to analogy and intelligence, and unconscious functions strictly connected with intuition. In the article, we show that an approach guaranteeing communicative success is connected to teaching formal aspects of language combined with meaning. In the first part, we discuss the specificity of both types of grammatical knowledge and refer to the concept of « grammar of sense » by P. Charaudeau. In the second part, some exercises and communication tasks combining analytical thinking and sense-oriented intuitive thinking are proposed.